Unveiling ignis fatuus: Microlightning between microbubbles - Yu Xia; Yifan Meng; Jianbo Shi; Richard N. Zare (Proceedings of the National Academy of Sciences, 2025)
Will-o’-the-wisps, ghostly blue flames seen at night in marshlands and long attributed to methane cool flames, have remained scientifically unexplained, a mystery caused by the lack of a known ignition mechanism. Here, we demonstrate that spontaneous electrical discharges, termed “microlightning”, can occur between rising methane-containing microbubbles in water. High-speed optical imaging reveals brief flashes between charged bubbles, arising from strong electric fields at curved gas–liquid interfaces. These discharges initiate nonthermal oxidation of methane, producing luminescence and measurable heat under ambient conditions. Our findings offer a scientific basis for ignis fatuus and reveal a general mechanism by which electrified interfaces can drive redox reactions in natural environments without the need for external ignition sources.